Appraisal of the papers of biomedical scientists and physicians for a medical archives. - Anderson, P G (1985)
Numerous medical libraries house archival collections. This article discusses criteria for selecting personal papers of biomedical scientists and physicians for a medical archives and defines key terms, such as appraisal, manuscripts, papers, records, and series. Appraisal focuses on both collection and series levels. Collection-level criteria include the significance of a scientist's career and the uniqueness, coverage, and accessibility of the manuscripts. Series frequently found among medically related manuscripts are enumerated and discussed. Types of organizational records and the desirability of accessioning them along with manuscripts are considered. Advantages of direct communication with creators of manuscripts are described. The initial appraisal process is not the last word: reevaluation of materials must take place during processing and can be resumed long afterwards.